THE FEAR OF LABOR AND THE ROLES OF MIDWIVES - Koroglu, Cemile Onat; Surucu, Sule Gokyildiz; Vurgec, Burcu Avcibay; Usluoglu, Feyruz (LIFE: International Journal of Health and Life-Sciences, 2017)
Pregnancy is a period in which women experience bio psychosocial changes and adapt to these changes. Women are prepared for labor and parenting. Despite the developments in health care services, many women are afraid of these processes even though the pregnancy, labor, and postnatal processes now result in relatively few complications. It is quite difficult to accurately define the fear of labor. One of the main factors of the fear of labor is the fear of unknown. Women may experience fear of labor, a process that is unpredictable, especially in pregnancy. Besides, the definition of the fear of pregnancy varies according to each woman who experience fear. Also, superstitious beliefs, the level of civilization of the society, and culture are the most important factors that affect women’s idea of pain, causing anxiety and fear of labor to be expressed differently. It is impossible to get rid of the fear of labor completely. An acceptable level of fear can help a woman prepare for her labor. However, the level of fear needs to remain at the optimal limits. For this, the woman has to learn to cope with the fear of labor. Midwives are the most important supporters in labor, and they also need to have sufficient knowledge and skills in this regard. With this paper, the frequency of fear of labor, the causes, the effect of this fear on hormonal balance and results, active communication with women who fail to cope with fear of labor, and about roles of midwives responsible for pre-pregnancy, pregnancy, labor and postnatal services have been compiled based on relevant literature and updated.